The Role of Technology Acceptance Model (TAM) in Improving Learning Performance: Study at Maritime Vocational High School in Central Java - Arika Palapa; Fakhruddin Fakhruddin; Sucihatiningsih Dian Wisika Prajanti; Tri Joko Raharjo (International Conference on Science, Education, and Technology, 2021)
The role of technology in the learning process in the current era is crucial to be used in enrichment and student learning experiences. Students use the learning process through the use of technology to obtain the expected competencies. Teachers as facilitators use CBT as a tool in facilitating the learning process. In the process, the problem that arises is the acceptance of students' perceptions or CBT technology. This study aims to examine the effect of the technology acceptance model (TAM) model on the learning performance of maritime vocational high school students. The study used a quantitative approach by using SEM-PLS in testing the data that had been obtained. This study involved 79 maritime vocational high school students from Central Java province. The results showed that there was an effect of perceived usefulness on behavioral intention and direct learning performance. In addition, perceived usefulness affects learning performance through behavioral intention, meaning that behavioral intention partially mediates perceived usefulness on learning performance. This study examines perceived ease of use on behavioral intention and learning performance. The results showed that it had a direct effect on behavioral intention but did not have a direct effect on learning performance. The study results indicate a role for the behavioral intention in mediating the total effect on learning performance.